The effectiveness of accuracy in cost estimation by using monte carlo simulation model - Siti Haifullia, Ayob (2013)
Estimation is a forecast tools which is predict the actual expenses of cost in a project should be. It is made to encourage the client on the progress of activity in each phase of the project that involves cost and also updating the client on the design of the project. This research is focused on time and cost management in a project. The variable that is controlled in this study is cost where as time is set as a fixed variable. Cost estimation in a project can be low, high or accurate. Alternatively, expenses that are involved in a project consist of direct cost and indirect cost. The objective that need to be achieved in this study are to identify factors affecting accurate cost estimation based on literature review studied and to suggest alternative method for cost estimation by using Monte Carlo simulation model. Besides, the problem statement that are discussed in this research are error in manual calculation of cost estimate, lack of experience in providing cost estimates from the new staff, difficulties to adjust the cost estimate for the changes in scope as the project develop and lastly providing estimates under pressure that are lead to inaccurate cost estimation. In order to provide accuracy for project budgeting, previous research has been studied to identify the current issues occurs in project management that are related to cost and time estimate and also the factors affecting accuracy of estimating. The literature review will discuss more on the overview of study of the effectiveness of accuracy cost estimating by using Monte Carlo simulation model. Existing technology and previous model on estimation of cost is discussing in this section. Besides, history of simulation system is also briefly explained. In methodology, the development of simulation process is discussed and the following method such as, company’s report and other sources are used in this study to collect data. Validity and reliability of thus research is also discussed. For finding, the chapter will include the table, distribution graph, calculation and also formula that is used in order to gain the results. In summary, the implication of the study is also included in this chapter. Furthermore, the theoretical and practical implications are discussing in detail to make this research more useful for future user. Limitation of the study is stated in this section so that it will help the future user to know the barriers when conducting this research.